Lymphoid Tissue–Resident Alcaligenes Establish an Intracellular Symbiotic Environment by Creating a Unique Energy Shift in Dendritic Cells - Hosomi, Koji; Shibata, Naoko; Shimoyama, Atsushi; Uto, Tomoya; Nagatake, Takahiro; Tojima, Yoko; Nishino, Tomomi; Takeyama, Haruko; Fukase, Koichi; Kiyono, Hiroshi; Kunisawa, Jun (Frontiers in Microbiology, 2020)
Lymphoid-tissue–resident commensal bacteria (LRCs), including Alcaligenes faecalis, are present in intestinal lymphoid tissue including the Payer’s patches (PPs) of mammals and modulate the host immune system. Although LRCs can colonize within dendritic cells (DCs), the mechanisms through which LRCs persist in DCs and the symbiotic relationships between LRCs and DCs remain to be investigated. Here, we show an intracellular symbiotic system in which the LRC Alcaligenes creates a unique energy shift in DCs. Whereas DCs showed low mitochondrial respiration when they were co-cultured with Escherichia coli, DCs carrying A. faecalis maintained increased mitochondrial respiration. Furthermore, E. coli induced apoptosis of DCs but A. faecalis did not. Regarding an underlying mechanism, A. faecalis—unlike E. coli—did not induce intracellular nitric oxide (NO) production in DCs due to the low activity of its lipopolysaccharide (LPS). Therefore, A. faecalis, an example of LRCs, may persist within intestinal lymphoid tissue because they elicit little NO production in DCs. In addition, the symbiotic DCs exhibit characteristic physiologic changes, including a low rate of apoptosis and increased mitochondrial respiration.